Involvement of Galectin-1 Tumor Microenvironment in Radiosensitivity - CHEN, YI-FAN; WANG, CHUNG-CHI; HSU, CHIEH-YING; HUANG, ENG-YEN (Anticancer research, 2021)
The mechanisms of galectin-1 in radioresistance may not only involve intracellular but also extracellular effects because galectin-1 can be secreted into the extracellular matrix. We, therefore, aimed to investigate the role of the galectin-1 tumor microenvironment on radiosensitivity in a murine tumor model. Wild-type or stable galectin-1-down-regulated cancer cells (melanoma (B16F10) and lung cancer (LLC1)) were injected (subcutaneous injection) into wild-type or knockout (galectin-1, B cells, and T cells) mice that were subject to 0 or 8 Gy irradiation. Galectin-1-down-regulated B16F10 cells showed increased radiosensitivity when injected into galectin-1 knockout mice. Interestingly, radioresistance of wild-type LCC1 tumors was noted when injected into galectin-1 and B cell knockout mice. However, radiosensitization was observed in T cell knockout mice with wild-type LCC1 cells. The role of endogenous galectin-1 in radioresistance exists in cases without extracellular galectin-1. Extracellular galectin-1 requires endogenous galectin-1 to radiosensitize tumors in mice.